Using FTT-CAN to the Flexible Control of Bus Redundancy and Bandwidth Usage - Silva, Valter (2012)
Controller Area Network (CAN) is a popular and very well-known bus system, both in academia and in industry, initially targeted to automotive applications as a single digital bus to replace the wiring that were growing complexity, weight and cost with the advent of new automotive appliances. However, requirements have evolved and CAN’s dependability and bandwidth limitations led to the emergence of alternative networks such as FlexRay and TTP/C. Nevertheless, we believe that it is possible to improve CAN so it could fulfill contemporary requirements. This paper proposes the use of Flexible Time-Triggered CAN (FTT-CAN) to increase the available bandwidth while providing fault tolerance in CAN based systems with multiple buses. The architecture and flexibility of FTT based systems enables a tight yet flexible control of redundancy and bandwidth usage without increasing the complexity of the nodes. In this novel solution, a FTT-CAN Master controls the dispatching of messages among a set of independent buses. The Master can react online to bus failures switching the transmission of critical messages to a non-faulty bus, always keeping a predetermined redundancy level.